2018
DOI: 10.2147/cmar.s181265
|View full text |Cite
|
Sign up to set email alerts
|

ESCO2 inhibits tumor metastasis via transcriptionally repressing MMP2 in colorectal cancer

Abstract: BackgroundEstablishment of cohesion 1 homolog 2 (ESCO2) plays important roles in the regulation of cohesion and genomic stability and has been implicated in human cancers. Yet, its clinical significance and biological function in colorectal cancer (CRC) are unknown.MethodsThe expression of ESCO2 was examined by quantitative real-time PCR, Western blot, and immunohistochemistry. The role of ESCO2 in the tumor metastasis of CRC and the related mechanisms were investigated using in vitro and in vivo models.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…Fumiichiro and Miyako examined the genes change, found that up‐regulation of ESCO2 was striking in breast cancer tissues and cell lines . Notably, the dysregulated ESCO2 was implicated to adjust metastatic activity in colorectal cancer (CRC), suppressing Matrix Metallopeptidase 2 (MMP2) . Yet, whether and how the progression of RCC is controlled by ESCO2 has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Fumiichiro and Miyako examined the genes change, found that up‐regulation of ESCO2 was striking in breast cancer tissues and cell lines . Notably, the dysregulated ESCO2 was implicated to adjust metastatic activity in colorectal cancer (CRC), suppressing Matrix Metallopeptidase 2 (MMP2) . Yet, whether and how the progression of RCC is controlled by ESCO2 has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…SLC16A10, coding for a member of a family of plasma membrane amino acid transporters, was shown to be significantly upregulated in higher-grade gliomas [52]; however, its role in glioma and other cancer types remains unclear. ESCO2, required for the establishment of sister chromatid cohesion during the S phase of mitosis [53], can enhance the malignancy of gastric cancer while inhibiting colorectal tumor metastasis [54,55], and its role in glioma has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein modulated the expression of histone acetyltransferases (Figure 2). The function of ESCO2 is to block MMP2 and help apoptosis [37]. Genistein upregulates the expression of ESCO2, which is likely to impact its anti-migratory response.…”
Section: Discussionmentioning
confidence: 99%